Sauer's manual of skin diseases - Hall, Brian J; Hall, John C (Wolters Kluwer Health, 2017)
Trusted by generations of medical students, residents, and non-specialist practitioners, Sauer’s Manual of Skin Diseases continues the tradition of excellence in the fully updated 11th Edition. This bestselling dermatology manual provides full-color photographs, step-by-step instructions, and easy-to-follow algorithms for diagnosis and treatment of all common skin conditions. The practical, user-friendly format consists of two distinct parts: the first part covers the diagnosis and management of the most commonly seen skin diseases. The second part is a comprehensive Dictionary-Index to the entire field of dermatology, including rare diseases and unusual dermatologic terms
Keywords: dermatovenerologie; kožní nemoci; Skin Diseases